CityGuide: a seamless indoor–outdoor wayfinding system for people with vision impairments - Cheraghi, Seyed Ali; Namboodiri, Vinod; Arsal, Güler (Universal access in the information society, 2024)
The accuracy of satellite-based positioning systems is poor in indoor environments and around built environments. Reading and following visual cues still remain the most common mechanism for providing and receiving wayfinding information in such spaces. This reliance on visual function for wayfinding puts individuals who are blind or visually impaired (BVI) at a great disadvantage, and there remains a great need to provide a low-cost, easy-to-use, and reliable wayfinding system within indoor and outdoor spaces that complements existing satellite-based systems. This paper presents the design, implementation, and evaluation of an initial prototype wayfinding system and smartphone application called CityGuide that can be used by BVI individuals to navigate their surroundings beyond what is possible with just a GPS-based system. CityGuide enables an individual to query and get turn-by-turn shortest route directions from an indoor location to an outdoor location. CityGuide leverages recently developed Bluetooth Low Energy (BLE) indoor wayfinding solutions in conjunction with satellite signals to provide a seamless indoor–outdoor navigation and wayfinding system that guides a BVI individual to their desired destination through the shortest route. Evaluations of CityGuide with BVI human subjects within an unfamiliar university campus scenario demonstrated its potential to be effective compared to other popularly used apps.